Tautomerization-mediated molecular switching between six- and seven-membered rings stabilized by hydrogen bonding - Storch, Golo; Spallek, Markus Jürgen; Rominger, Frank; Trapp, Oliver (Chemistry - a European journal, 2015)
Abstract 1,3,4,6-Tetraketones typically undergo keto?enol tautomerism forming bis-enols stabilized by intramolecular hydrogen bonding in two six-membered rings. However, 1,3,4,6-tetraketones derived from the terpene ketone camphor and norcamphor exist as isomers with two distinguishable modes of intramolecular hydrogen bonding, namely, the formation of six- or seven-membered rings. The structural requirements for this so far unknown behavior were investigated in detail by synthesis and comparison of structural analogues. Both isomers of such 1,3,4,6-tetraketones were fully characterized in solution and in the solid state. Intriguingly, they slowly interconvert in solution by means of tautomerism?rotation cascades, as was corroborated by DFT calculations. The influence of temperature and complexation with the transition metals Pd, Rh, and Ir on the interconversion process was investigated.
Gesehen am 24.06.2020